2016
DOI: 10.21307/jofnem-2017-018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nutrient Concentration, Addition of Thickeners, and Agitation Speed on Liquid Fermentation of Steinernema feltiae

Abstract: Entomopathogenic nematode production in liquid fermentation still requires improvements to maximize efficiency, yield, and nematode quality. Therefore, this study was aimed at developing a more suitable liquid medium for mass production of Steinernema feltiae, by assessing the effects of nutrient concentration, thickeners (primarily agar), and agitation speed on infective juvenile (IJ) yield. Base medium (BM) contained yeast extract (2.3%), egg yolk (1.25%), NaCl (0.5%), and corn oil (4%). All media were inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…In our study, the highest concentration of IJs was 9.5 × 10 5 IJs/g medium excluding the weight of water and thus the value was really higher than that reported by Ramakuwela et al (2016). This result was close to the value reported when using basic medium in liquid culture with an agitation speed 280 rpm (Leite et al, 2016b). In another study, 9.7 × 10 5 IJs/g medium (after 15 d incubation) was achieved using chicken offal medium (Tabassum and Shahina,Figure 3: Effect of insect powder and dose level on the progeny yield (h) of Spodoptera litura larvae in two trials.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, the highest concentration of IJs was 9.5 × 10 5 IJs/g medium excluding the weight of water and thus the value was really higher than that reported by Ramakuwela et al (2016). This result was close to the value reported when using basic medium in liquid culture with an agitation speed 280 rpm (Leite et al, 2016b). In another study, 9.7 × 10 5 IJs/g medium (after 15 d incubation) was achieved using chicken offal medium (Tabassum and Shahina,Figure 3: Effect of insect powder and dose level on the progeny yield (h) of Spodoptera litura larvae in two trials.…”
Section: Discussionsupporting
confidence: 84%
“…The mixture of eggs juveniles, males, and residue of females was rinsed three times in sterile distilled-water. Then the mixture suspension (1-2 drops) was transferred to wells of a 24-well culture plate with 0.3 mL of TSB+Y medium in each well and incubated at 25°C for 2 d and then used for inoculum (Leite et al, 2016b).…”
Section: Nematode Axenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiological research frequently involves cell culture experiments using chemically defined synthetic media in small flasks. In biotechnological research, the applicability of such laboratory generated data to industrial conditions is of primary importance (Farid et al , Ercan et al , Jayakar and Singhal , Saad et al , Ibrahim et al , Leite et al ). In wine microbiology, it has already been reported that several parameters influence the successful completion of the fermentation and the production of desirable flavour compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Xenorhabdus bovienii isolation and S. feltiae axenization were done according to Leite et al (2016).…”
Section: Methodsmentioning
confidence: 99%